Realisme Magis dalam Crita Cekak Berjudul Kerisku Kasangsaranmu Karya Suparto Brata - Fitria, Ajeng Aisyah (Javanese Language, Literature, and Culture Study Program, Universitas Gadjah Mada, 2024)
Literary works are considered the result of human reflection on the realist world. However, some literary works contain not only realist but also topics of magic, such as in the short story (cerkak) titled Kerisku Kasangsaranmu by Suparto Brata in the book Trem Anthology of Crita Cekak (2000). This study uses the theory of magical realism to uncover the magical nature of a realist literature. This theory is defined as an understanding that presents magical or irrational things that live in modern literary works. This study focuses on analyzing the characteristics and determining the level of magical realism. This research uses a qualitative method. The theory of magical realism characteristics from Wendy B. Faris explains about five characteristics of magical realism, namely 1) irreducible elements, 2) phenomenal world, 3) unsettling doubt, 4) merging realms, 5) disruption of time, space, and identity. Based on the results of the analysis, it was discovered that the short story Kerisku Kasangsaranmu has all the characteristics, so it could be categorized as a work of magical realism. The level between realist and magical in the cerkak is more prominent in the magical, resulting in realist or real things being covered by magics. This can be seen from the role of the 'naughty' keris which is more emphasized as the main conflict in the story. === Karya sastra dianggap sebagai hasil cerminan manusia terhadap dunia yang realis. Meskipun demikian, beberapa karya sastra tidak hanya mengandung hal-hal realis tetapi juga magis, seperti pada crita cekak (cerkak) berjudul Kerisku Kasangsaranmu karya Suparto Brata yang termuat dalam buku Trem Antologi Crita Cekak (2000). Kajian ini menggunakan teori realisme magis untuk membongkar hal-hal yang bersifat magis dalam karya sastra realis. Teori ini didefinisikan sebagai suatu paham yang menghadirkan hal-hal magis atau irrasional yang hidup pada karya sastra modern. Penelitian ini berfokkus pada analisis karakteristik dan penentuan kadar realisme magis. Metode yang digunakan yaitu metode kualitatif. Teori karakteristik realisme magis dari Wendy B. Faris menerangkan tentang lima karakteristik realisme magis, yakni 1) irreducible element, 2) phenomenal world, 3) unsettling doubt, 4) merging realms, 5) disruption time, space, and identity. Berdasarkan hasil analisis, ditemukan bahwa cerkak Kerisku Kasangsaranmu memiliki semua karakteristik, sehingga dapat dikelompokkan sebagai karya realisme magis. Kadar antara realis dan magis dari cerkak tersebut lebih menonjol pada hal magis sehingga mengakibatkan hal-hal yang realis atau nyata tertutupi oleh hal magis. Hal ini dapat dilihat dari peran keris ‘nakal’ yang lebih ditonjolkan sebagai permasalahan utama dalam cerkak tersebut.